Safety, Pharmacokinetics/Pharmacodynamics, and Absolute Bioavailability of Dexmedetomidine Hydrochloride Nasal Spray in Healthy Subjects: A Randomized, Parallel, Escalating Dose Study - Kuang, Yun; Wang, Sai-Ying; Wang, Meng-Na; Yang, Guo-Ping; Guo, Can; Yang, Shuang; Zhang, Xing-Fei; Yang, Xiao-Yan; Pei, Qi; Zou, Chan; He, Yan-Hong; Zhou, Ying-Yong; et al. (Frontiers in Pharmacology, 2022)
Background: The present study evaluated the safety, pharmacokinetics/pharmacodynamics (PK/PD), and absolute bioavailability (Fabs) of Dex nasal spray in healthy adult subjects, which serves as a bridge for the subsequent study in children. Methods: Part 1: a double-blind, placebo-controlled, single ascending dose study was performed on 48 subjects. For 20-/40-μg groups, every 6/2 subjects received either Dex/placebo nasal spray or Dex/placebo injection in two periods. In total, 12/4 subjects each received 100 μg Dex/placebo nasal spray. Part 2: a randomized, double-blind, placebo-controlled study; 12/4 subjects received 150 μg Dex/placebo nasal spray. Part 3: a randomized, open, self-crossover study; 12 subjects received 20 μg and 100 μg Dex nasal spray in two periods alternately. The method of administration was optimized in Part 2 and Part 3. Results: In part 1, Dex nasal spray was well tolerated up to the maximum dose of 100 μg, whereas the Fabs was tolerated to only 28.9%–32.3%. In Part 2 and Part 3, the optimized nasal spray method was adopted to promote the Fabs of Dex nasal spray to 74.1%–89.0%. A severe adverse event was found in Part 2. In Part 3 (100 μg), the Ramsay score increased the most and lasted the longest, whereas the BIS score decreased most significantly. Conclusion: Using the optimized nasal spray method, a single dose of 20/100 μg of the test drug was safe and tolerable, and 100 μg may have approached or reached the plateau of sedation. In addition, it is found that the optimized method can greatly improve the bioavailability of the test drug, leading to its higher reference value.